Formação profissional em serviço social: embates no estágio entre o projeto ético-político e as demandas do mercado de trabalho - Araújo, Ana Quércia Pereira de (2010)
The objective of this study is to examine in the Vocational training, clashes between the goals ethical-political of profession and determinations of the labor market during the supervised training in Social Work, session 2010.1 UFPB. This theoretical work valid in critical-dialectical perspective methodology, consist in investigation in 06 institutions, where were interviewed the respective 06 social workers supervisor training field, and 12 students trainees, whose testimonials were confronted face of adversity working conditions, and elements that make it difficult the materialization of professional project. The quantitative and qualitative research resulted in the identification of the single side of the technical-operational dimension negatively influences in conducting the activities of the trainees, despite the bureaucratization of the activities, most reveals not find able for labor market stage due to the fact limited to only one field. For the professional field supervisors, the project viability ethical-political direction depends on a critical, but still understands as their professional role assignments made by the institution, which signal an exacerbation of technical efficiency, required by the rationalization of work. These data demonstrate one of the biggest challenges of professional training is realize overcoming these weaknesses from stage, it has direct results on professional performance spaces developed in occupational areas outlined by the labor market.